Management Science and Big Data: A Text Mining Meta-Analysis Study - Asllani, Arben; Long, D. Michael (Journal of Management Policy and Practice, 2018)
This study explores the impact of Big Data on the major research fields of management science. Textmining and exploratory factor analysis are applied on articles published in the Management Science journal from 1998-2017 to measure changes in general trends, models, and methodologies. The findings show a significant shift in the underlying research themes in management science over this period. However, despite the Big Data buzz, there is no significant increase over the study period in Big Data categories. Although, the results did show a recent significant correlation between specific themes and Big Data models and techniques.